Synthesis, antiproliferative and antifungal activities of 1,2,3-triazole-substituted carnosic acid and carnosol derivatives - Pertino, Mariano Walter (2015)
Fil: Fil: Pertino, Mariano Walter. Universidad de Talca. Instituto de Química de Recursos Naturales; Chile.